Analysis of the Need for Interactive Learning Media in Developing Learning with a Literacy and STEAM Approach - Prastyaningrum, Ihtiari; Alfina, Alisa; Wisesa, Rizky Dwi (Journal of Instructional and Development Researches, 2025)
The implementation of learning at the early childhood education level will never be separated from what is called learning media. The learning media used must be able to be a tool to help transfer knowledge from teachers to their students. The use of learning media by teachers must also be accompanied by the teacher's understanding of what knowledge will be transferred with the help of the media. As is well known, currently learning at the early childhood level is directed at learning with a Literacy and STEAM approach. Therefore, the existence of appropriate learning media is needed. This study aims to analyze the need for interactive learning media that can support the implementation of learning activities with a Literacy and STEAM approach. The observation and in-depth interview methods supported by questionnaires are steps to obtain research results. The results of this study indicate that early childhood needs learning media that can accommodate science, technology, engineering, art, and mathematics. However, the pedagogical competence and literacy quality of a teacher are also important factors so that the use of learning media can be maximized. In relation to the results obtained, it is suggested that in the future learning media containing the five STEAM disciplines can be accommodated, so that it is hoped that the implementation of the STEAM approach in learning can run more optimally.